ELEPHANTOPUS SCABER AND SAUROPUS ANDROGYNUS REGULATE MACROPHAGES AND B LYMPHOCYTE CELLS DURING SALMONELLA TYPHI INFECTION - Muhammad Sasmito Djati; Dinia Rizqi Dwijayanti; Lulut Dwi Nurmamulyosari; Yayu Fuadah; Muhammad Basyarudin; Nur Jannah (UNEJ e-Proceeding, 2016)
Abstract—Macrophages and B lymphocyte play an important role as the first cell type to encounter bacterial pathogen and as a mediator that initiate the adaptive immune response. Those types of cell can die in many ways such as apoptosis, necrosis, pyroptosis and autophagy during the host cell-pathogen recognition. This study aimed to investigate the ability of E. scaber and S. androgynus formula in regulating macrophage and B lymphocyte cells during bacterial infection. The pregnant mice were randomly divided into seven experimental groups: T1 (control), T2 (S. typhi infection), T3 (S. typhi, E. scaber 100%), T4 (S. typhi, E. scaber 75% and S. androgynus 25%), T5 (S. typhi, E. scaber 50% and S. androgynus 50%), T6 (S. typhi, E. scaber 25% and S. androgynus 75%), and T7 (S. typhi, S. androgynus 100%). Flowcytometry analysis was performed on day 18. S. typhi infection decrease the formation of macrophage and B lymphocyte cells in bone marrow and induce cell death in PBMC. We clearly proved that E. scaber 75% and S. androgynus 25% formula was able to ameliorate the formation of macrophage and B lymphocyte cells in BM. While E. scaber 25% and S. androgynus 75% formula increased the relative number of macrophage and B lymphocyte cells in PBMC.